2019
DOI: 10.1002/aisy.201900035
|View full text |Cite
|
Sign up to set email alerts
|

Small‐Scale Robots in Fluidic Media

Abstract: One of the most promising uses of miniature robots (MRs) in the biomedical field is performing local in situ diagnosis and therapy. Researchers have proposed numerous swimming methods utilizing various actuation principles. Herein, the different propulsion methods of MRs are evaluated by analyzing their scalability. Comparing various actuators, how their performance changes with size reduction is evaluated. The swimming of natural flagellar swimmers such as spermatozoa and nematodes is analyzed. It is found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 112 publications
(181 reference statements)
0
6
0
Order By: Relevance
“…The robotic pill is rotated along its longitudinal axis, producing displacement by each magnetic field turn. [46][47][48][49][50][51] The robotic pill can be guided through predetermined paths, as illustrated in Figure 4b, which shows the overlap of multiple images taken from Video S3, Supporting Information. This locomotion mechanism can be used to navigate the structure over complex and uneven routes.…”
Section: Resultsmentioning
confidence: 99%
“…The robotic pill is rotated along its longitudinal axis, producing displacement by each magnetic field turn. [46][47][48][49][50][51] The robotic pill can be guided through predetermined paths, as illustrated in Figure 4b, which shows the overlap of multiple images taken from Video S3, Supporting Information. This locomotion mechanism can be used to navigate the structure over complex and uneven routes.…”
Section: Resultsmentioning
confidence: 99%
“…The robotic pill is rotated along its longitudinal axis, producing displacement by each magnetic field turn. (Tu and Gao, 2020;Hu et al, 2018;Lee et al, 2022;Xu et al, 2022;Sayed et al, 2022;Kosa and Hunziker, 2019) The robotic pill can be guided through predetermined paths, as illustrated in Figure 5c, which shows the overlap of multiple images taken from Video S3.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…Moreover, being observable enables flexible actuator manipulations including rotation, lifting, and flipping. The fine motion control of magnetic actuators makes it possible to precisely locate and even tune the force exerted on the inner wall of the intestine [ 40 ], uterus [ 103 ], and stomach [ 104 , 105 ]. Hwasaki et al reported a soft patch remover driven by a magnetic actuator, shown in Figure 3 d [ 106 ].…”
Section: Actuators For Various In Vivo Biomedical Applicationsmentioning
confidence: 99%